Manipal manual of clinical biochemistry - Nayak B, Shivananda; Gurumadva Rao, S (India : Jaypee Brothers Medical Publishers, 2013)
A textbook will be improved only by successive revisions. I tired to keep up my promise of revising this book every two-three years. I always respect the suggestions and constructive criticims that come from the readers.
Contents 1. Introduction to clinical biochemistry 2. Specimen collection and handling 3. Centrifugation techniques 4. Spectrophotometry and colorimetry 5. Electrophoresis 6. Chromatolography 7. Immunochemical techniques (RIA and ELISA) 8. Carbohidrates 9. Hormones 10. Plasma proteins 11. Tumor markers Y otros catorce capítulos más Index
Incluye Contents
Incluye Index
Keywords: BIOCHEMISTRY; CLINICAL BIOCHEMISTRY